2018
DOI: 10.2987/17-6683.1
|View full text |Cite
|
Sign up to set email alerts
|

Report of Chikungunya Virus in Wild Populations of Aedes aegypti in Guerrero State, Mexico

Abstract: We detected vertical transmission of chikungunya virus (CHIKV) in wild populations of Aedes aegypti from San Marcos, Guerrero, Mexico, with real-time reverse transcriptase-polymerase chain reaction. A total of 20 pools (1-11 specimens/pool) of larvae, male, and female mosquitoes were tested. We report the detection of CHIKV in 2 of 11 larval pools, 4 of 5 male pools, and 1 of 4 female pools, from field-collected mosquitoes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Populations of Ae. aegypti males collected in Mexico [42] and Thailand [43] have also been identified to be naturally infected with CHIKV. It has been shown that the high vector competence of both Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of Ae. aegypti males collected in Mexico [42] and Thailand [43] have also been identified to be naturally infected with CHIKV. It has been shown that the high vector competence of both Ae.…”
Section: Discussionmentioning
confidence: 99%